Análise da atividade docente: em busca dos sentidos e significados constituídos pelo professor acerca das dificuldades de aprendizagem - Brando, Maria Fourpome (2012)
The objective of this research was to investigate the senses and meanings constituted by a teacher about the "learning difficulties" of her pupils. The theoretical and methodological framework adopted was that of the sociocultural approach in Psychology, as well as the one proposed by the Clinical Activity. The research subject was a first-grade teacher, teaching the first year of basic schooling. Data collection involved the use of different techniques: a) observations and video recordings of classes taught by the teacher; b) selection of excerpts filmed and edited - short episodes - in order to illustrate teaching aspects related to the "learning difficulties"; c) interviews with the teacher, seeking to go deeply into issues related to her professional activity; d) sessions of simple self-confrontation (ACS) and crossedconfrontation (ACC), in which the teacher, alone and/or monitored, watched and analyzed episodes in which she was teaching her students. The self-confrontation sessions were videotaped and transcribed. From this material and the one collected by the interview, it was adopted the procedures proposed by Aguiar and Ozella (2006) to reach nuclei of meaning. The core analysis indicated that the senses and meanings constituted by the teacher about the "learning difficulties" of her students were articulated, first, to the importance of the pedagogical practice in providing a good quality of teaching activity, one capable of meeting the needs of students with different learning paces; and, second, to the fact that this will only occur through professional relationships. Going deep in the observation and analysis of one s own activity, making the teacher an observer of herself during the professional activity, provided her with the necessary critical distance to see problems in it that by and via discussion with the researcher, provided opportunities to transform her teaching